EDUKASI NUTRISI SEIMBANG UNTUK HIDUP LEBIH SEHAT PADA LANSIA DENGAN PENYAKIT KRONIS - Suzan, Raihanah; Halim, Samsirun; Ayudia, Esa Indah; Miftahurrahmah, Miftahurrahmah (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2024)
ABSTRACTThe elderly population is projected to increase from 841 million in 2013 to 2 billion by 2050, accounting for 21% of the total global population. The elderly are susceptible to chronic diseases, necessitating balanced nutrition education to help them lead healthier lives despite chronic conditions. This Community Service Activity (CSA) was conducted at the Koni Health Center in Jambi city. Participants underwent anthropometric examinations for chronic disease screening and received education through leaflets and counseling on balanced nutrition for the elderly with chronic diseases. The activity was attended by 46 participants, with the majority being 22 participants (47.8%) aged 60 to 69 years, 29 participants (63%) were female, 24 participants (52.2%) had a nutritional status of grade 2 obesity, only 4 participants (8.7%) did not have any chronic disease, and 36 participants (78.3%) had more than one chronic disease. The average pre-test score was 34.78, and the post-test score was 70.43, indicating an increase in participants' knowledge following education on balanced nutrition for the elderly with chronic diseases.Keywords: balanced nutrition, elderly, chronic diseases ABSTRAKPopulasi lanjut usia (lansia) diperkirakan meningkat dari 841 juta orang di tahun 2013 menjadi 2 milyar orang pada tahun 2050, atau 21% dari total populasi dunia. Lansia rentan menderita penyakit kronis, sehingga perlu dilakukan edukasi nutrisi seimbang supaya lansia dengan penyakit kronis dapat hidup lebih sehat. Kegiatan Pengabdian Pada Masyarakat (PPM) ini dilaksanakan di Puskesmas Koni kota Jambi. Peserta menjalani pemeriksaan antropometri untuk skrining penyakit kronis dan menerima edukasi berupa pemberian leaflet dan penyuluhan terkait nutrisi seimbangpada lansia dengan penyakit kronis. Kegiatan diikuti oleh 46 orang peserta, sebagian besar peserta yaitu 22 orang peserta (47,8%) berusia 60 hingga 69 tahun, 29 orang peserta (63%) berjenis kelamin perempuan, 24 orang peserta (52,2%) dengan status nutrisi obesitas derajat 2, hanya 4 orang (8,7%) yang tidak mengidap penyakit kronis, dan 36 orang peserta (78,3%) mengidap lebih dari satu penyakit kronis. Dengan rerata nilai pre tes 34,78 dan nilai post tes 70,43. Terjadi peningkatan pengetahuan peserta pengabdian setelah dilakukan edukasi terkait nutrisi seimbang pada lansia dengan penyakit kronis. Kata kunci: nutrisi seimbang, lansia, penyakit kronis